Ergonomia do posto de trabalho em máquinas de colheita da madeira - Paini, Anderson De Costa (2016)
With the increase of mechanization, the timber harvesting operations are now executed with modern machines, improving working conditions when compared to manual systems. However, such machines can still offer unfavorable ergonomic conditions to operators in terms of internal dimensions of the workstation, body postures, repetitive movements and noise emission. Therefore, the objective of this study was to perform an ergonomic analysis in the workstation of timber harvesting machines, in order to contribute to the improvement of the conditions of comfort, safety and health of forest operators. The study was conducted in the operational areas of timber harvesting of a forestry company located in the city of Curiúva, State of Paraná, Brazil, in stands of Pinus taeda L., and involving 12 operators of feller-bunchers, skidders, processor and forest loaders. The ergonomic analysis of the job included the internal dimensions of the booths using the Skogforsk methodology, analyzing six parameters and framing the cabin in ergonomic classes A, B, C, D and 0 (zero). For postural analysis there were installed two cameras inside the machine, and the shoots were viewed with MSShow software and analyzed with the REBA (Rapid Entire Body Assessment) and RULA (Rapid Upper Limb Assessment) methodology. The analysis of repetitive hand movements was performed by the movies of the operators in the workstation using the Latko scale, Silverstein’s Criteria and SI (Strain Index) method. Postural discomfort was analyzed with the use of a map of body segments adapted from Corlett, through individual interviews with operators. Finally, an analysis of the occupational exposure to noise using a set audio-dosimeter installed in the hearing zone of operators, and the results were compared with Annex 1 of Regulatory Standard N° 15. The results showed a classification B for feller-buncher, processor and forest loader cabs and classification C for skidder cab. In the postural analysis there were identified 7 typical postures adopted by the operators in all machines, being the most of these showed some biomechanical risk caused by the inclination of the trunk and neck, repetitiveness of hands and wrists movements and standing for long periods in static position. The Latko scale ranked the repetitive hand movements with a score of 8 to the feller-buncher, processor and forest loader and 6 for the skidder, in addition to the Silverstein’s criteria classified all activities as highly repetitive. The SI method presented score 20,3 for the feller-buncher, processor and forest loader and 9,0 for the skidder, showing high risk of Repetitive Strain Injuries and/or WorkRelated Musculoskeletal Disorders (RSI/WMSDs). The map of body segments indicated discomfort in the eye, hands, shoulders, knees and lower back regions, justified by the shift of the night, repetitiveness and inadequate postures. For noise levels were found 73 dB (A) for the feller-buncher, 82 dB (A) for the skidder, 68 dB (A) for forest processor and 83 dB (A) for the forest loader, with the action level exceeded the recommended by Brazilian legislation (80 dB (A)) for eight hours of work) for the skidder and forest loader, therefore, recommending the use of hearing protectors. Finally, the unfavorable conditions in the workplace may lead to the adoption of inappropriate postures with risk of RSI/WMSDs as well as damage to the auditory system of forest operators.